2005
DOI: 10.1086/427242
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Severe Acute Respiratory Syndrome–Associated Coronavirus–Neutralizing Human Monoclonal Antibody That Provides Effective Immunoprophylaxis in Mice

Abstract: Two neutralizing epitopes were defined for MAbs to SARS-CoV S glycoprotein. Antibodies to both epitopes protected mice against SARS-CoV challenge. Clinical trials are planned to test MAb 201, a fully human MAb specific for the epitope within the receptor-binding region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
177
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 23 publications
7
177
0
Order By: Relevance
“…However, there is no direct evidence that patients with SARS had previous exposure to a related virus. Also, macrophages are not productively infected by SARS-CoV, and there was no evidence of enhanced disease in animals that were infected with SARS-CoV following passive transfer of antibodies against SARSCoV induced by infection or immunization (68, [141][142][143][144].…”
Section: Humoral Immune Response To Sars-cov Infectionmentioning
confidence: 99%
“…However, there is no direct evidence that patients with SARS had previous exposure to a related virus. Also, macrophages are not productively infected by SARS-CoV, and there was no evidence of enhanced disease in animals that were infected with SARS-CoV following passive transfer of antibodies against SARSCoV induced by infection or immunization (68, [141][142][143][144].…”
Section: Humoral Immune Response To Sars-cov Infectionmentioning
confidence: 99%
“…The main receptor for SARS-CoV is angiotensin-converting enzyme 2 (ACE2) [7], and it has been shown that amino acids 318-510 of the SARS-CoV S protein are sufficient to bind to ACE2 [8,9]. The S protein is an attractive target for both therapeutics and vaccine development because monoclonal antibodies to the S protein can neutralize SARS-CoV infection [10,11]. Moreover, the S protein has been shown to induce serum neutralizing antibodies and confer protective immunity against SARS-CoV challenge [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several epitope sites, defined by polyclonal or monoclonal antibodies, have been identified on the S protein, depending on experimental conditions, all lying within wide or narrow regions between a.a. 12-1,192 20., 21., 22., 23., 24., 25., 26., 27., 28., 29., 30., 31.. Defining conserved immunodominant epitope regions of the S protein is of crucial importance for future anti-SARS vaccine development.…”
Section: Introductionmentioning
confidence: 99%